Effectiveness of an Educational Program on Nurse’s Knowledge and Practices Regarding Assessment and Care Management for Wounds at Intensive Care Unit and Surgical Wards in General Kirkuk Hospital - Hazaa, Noora A.; Mansour , Kalida Alwan (International Journal of Psychosocial Rehabilitation, 2020)
Objective(s): This study aims to evaluate the effectiveness of an educational program on surgical nurse’s knowledge regarding assessment and care management for wounds at intensive care unit and surgical wards in general Kirkuk hospital, and to find out the relationships between nurse’s knowledge and practices and their socio- demographic characteristics (age, gender, level of education, years of experience in nursing, years of experience in intensive care unit or surgical wards, and participation in training session). Methodology: A quasi-experimental design (descriptive study) used to guide this study, it was conducted by use of pre-post test approach for two groups of samples (case and control) during the period 15th of November, 2019 to 19th of April, 2020. A non-probability (purposive) sampling has been performed during a selection of (60) nurses who works in the intensive care unit and surgical wards in general Kirkuk hospital were divided into two groups; (30) nurses as a case group who were exposed to the educational program and (30) nurses who are not exposed to the educational program considered as a control group. In order to reach the aims of the study, the researcher constructed program and questionnaire and observational checklist format to assess the nurses` knowledge and practices, the questionnaire format was composed of the five domains(50) questions and observational checklist to assess nurses` practices was composed of five domains (51) items. The validity of the program and instrument was determined by presenting it to (23) specialist experts and reliability of the instruments was determined through (test-retest) approach for knowledge test, while the reliability of observational checklist was determined through the inter and intra-examiner. The data analyzed through the use of a descriptive and inferential statistics in order to discover the differences between the case and control groups. Result: The findings of the current study revealed that there are highly statistically significant differences in post test between case and control groups in all knowledge parts and practice domains at P equal or less than 0.001. The findings also show that there is a statistical association between nurses` knowledge and their educational qualification, while the results show there is no statistically association between nurses` practices and their demographic characteristics. Conclusion: The study concluded that the effectiveness of an educational program on nurses knowledge and practices regarding assessment and care management of wounds is positive at a high rate. Recommendations: Based on the findings of current study the researcher recommended that the educational and training programs should be conducteed periodically for nurses, also should provide the tools and chart that specially used to assess wound in a general and pressure ulcer in a particular in all surgical wards and units in order to enhance the level of their knowledge and to achieve optimal practices regarding assessment and care management for wounds, the researcher also recommended the necessity of conducting more research studies in other provinces of Iraq.